2017
DOI: 10.1103/physrevd.96.026015
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity bound for anisotropic superfluids with dark matter sector

Abstract: The shear viscosity to the entropy density ratio η/s of the anisotropic superfluid has been calculated by means of the gauge/gravity duality in the presence of the dark matter sector. The dark matter has been described by the Yang-Mills field analogous to the one describing visible matter sector and it is assumed to interact with the visible field with coupling constant α. Close to the superfluid transition temperature (Tc) the analytical solution has been given up to the leading order in a symmetry breaking p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…We will not perform this analysis in this paper and content ourselves with the meta-stability of this solution implied by the energy arguments. A similar result was derived in [25] when considering vortices in the presence of an additional U (1) gauge sector.…”
Section: Free Energysupporting
confidence: 60%
See 1 more Smart Citation
“…We will not perform this analysis in this paper and content ourselves with the meta-stability of this solution implied by the energy arguments. A similar result was derived in [25] when considering vortices in the presence of an additional U (1) gauge sector.…”
Section: Free Energysupporting
confidence: 60%
“…This was recently interpreted as a dark sector in holographic vortex applications [25]. However, it seems plausible that coupling of both scalars to the original U (1) gauge field might be sufficient to find non-Abelian vortex solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The other strong coupling effects include the upward curvature seen in the temperature dependence of the upper critical field calculated via AdS/CFT correspondence [15][16][17][18][19]. It leads to the value of zero temperature magnetic field higher than the estimate based on the equation [20]:…”
Section: Strong Coupling Effects In Holographic Superconductorsmentioning
confidence: 88%
“…Working in the probe limit we have found that dark matter sector affects various properties of the holographic superconductors depending on their symmetry and other details. In particular the superconducting transition temperature T c of the s-wave superconductor with dark matter (DM) is modified as T = T c /α 1/6 , while in the Maxwell vector p-wave holographic superconductor with dark matter sector and for real components of the vector field gives us the same description of the phase transitions as the s-wave model [15][16][17][18][19]. It is worth noting the dependence of the superconducting transition temperature T c on the charge density ρ, which is T c ∝ ρ 1/3 .…”
Section: Some Resultsmentioning
confidence: 99%
See 1 more Smart Citation